RETRACTED: Assessment of the sustainable development of the flight route - Lebedev Georgy; Severov Vyacheslav; Mikhailin Denis; Roumakina Alena; Kostyshak Mikhail (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001